Studies on Pseudomonas aeruginosa Infection in Hatcheries and Chicken - ERAKY, R. D.; ABD EL-GHANY, W. A.; SOLIMAN, K. M. (Journal of the Hellenic Veterinary Medical Society, 2020)
The aim of this work was to spot light on the presence of Pseudomonas aeruginosa (P. aeruginosa) strains in hatcheries and dead in shell embryos. A total of 406 samples representing 200 and 206 swabs from hatcheries environment and yolk sacs of dead in shell embryos were collected from Damietta governorate, Egypt. P. aeruginosa was isolated and identified. Some virulent genes (toxA, psIA and fliC) of P. aeruginosa were detected using polymerase chain reaction (PCR). The antimicrobial susceptibility of P. aeruginosa was tested in vitro. Day and 11 days old broiler chicks were challenged with P. aeruginosa to determine the pathogenicity of the isolated strains. The results showed that P. aeruginosa was recovered from 16 (8%) out of 200 hatcheries and from 17 (8.25%) out of 206 chicken embryos samples. Isolated strains of P. aeruginosa showed presence of toxA, psIA and fliC virulent genes. P. aeruginosa strains were sensitive (100%) to ciprofloxacin, levofloxacin and gentamycin but resistant (100%) to amoxycillin/clavulanic acid, doxycycline and erythromycin. The pathogenicity test of day and 11 days old chicks revealed that P. aeruginosa was highly pathogenic induced mortality rates of 72 and 40%, respectively. Septicaemia of internal organs, unabsorbed yolk sacs, pneumonia, greenish exudates in the abdominal cavity, liver necrosis and enteritis were the predominant lesions. Histopathological changes supported the previous lesions. In conclusion, P. aeruginosa is of great importance pathogen of embryos and newly hatched chicks based on presence of virulent genes as well as in vivo pathogenicity study; respectively.